The Work Environment as a Variable of Intervening Compensation and Work Facilities For Job Satisfaction at PT. Telkom Aksess Balikpapan - Jatmiko, Novi Satria; Nurhalimah, Siti (The Graduate School of Sahid University, 2025)
This study aims to analyze the role of the Work Environment as an intervening variable of Compensation and Work Facilities for Job Satisfaction at PT. Telkom Aksess Balikpapan. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The object of the research is the employee of PT. Telkom Aksess Balikpapan with a sample of 59 employees. Data collection was carried out through the dissemination of questionnaires The results of the study showed that the Compensation has a significant effect on the Work Environment, Work Facilities also have a significant influence on the Work Environment, a good Work Environment contributes significantly to Job Satisfaction, Compensation has a direct influence that is not significant on Job Satisfaction, Work Facilities also have a direct influence on job satisfaction, Work Environment was able to function as a full mediator in Compensation for Job Satisfaction, as well as as serve as a partial mediator in Work Facilities for Job Satisfaction.